About symbolic violence in adolescent intergeneric relationships - Solarte-Muñoz, Maiber; Ortiz-Duque, Paula Andrea (Prospectiva. Revista de Trabajo Social e Intervención Social, 2003)
The verbal language allows us to approach the representations that the adolescents configure according to the appellatives used in the intergeneric relationships, with which we can verify the existence of hierarchies regarding the woman, stereotypes and the fear of exclusion, fundamentals of symbolic violence.